Permeant anions contribute to voltage dependence of ClC‐2 chloride channel by interacting with the protopore gate - Sánchez‐Rodríguez, Jorge E.; De Santiago‐Castillo, José A.; Arreola, Jorge (The Journal of physiology, 2010)
It has been shown that the voltage (Vm) dependence of ClC Cl− channels is conferred by interaction of the protopore gate with H+ ions. However, in this paper we present evidence which indicates that permeant Cl− ions contribute to Vm‐dependent gating of the broadly distributed ClC‐2 Cl− channel. The apparent open probability (PA) of ClC‐2 was enhanced either by changing the [Cl−]i from 10 to 200 mm or by keeping the [Cl−]i low (10 mm) and then raising [Cl−]o from 10 to 140 mm. Additionally, these changes in [Cl−] slowed down channel closing at positive Vm suggesting that high [Cl−] increased pore occupancy thus hindering closing of the protopore gate. The identity of the permeant anion was also important since the PA(Vm) curves were nearly identical with Cl− or Br− but shifted to negative voltages in the presence of SCN− ions. In addition, gating, closing rate and reversal potential displayed anomalous mole fraction behaviour in a SCN−/Cl− mixture in agreement with the idea that pore occupancy by different permeant anions modifies the Vm dependence ClC‐2 gating. Based on the ec1‐ClC anion pathway, we hypothesized that opening of the protopore gate is facilitated when Cl− ions dwell in the central binding site. In contrast, when Cl− ions dwell in the external binding site they prevent the gate from closing. Finally, this Cl−‐dependent gating in ClC‐2 channels is of physiological relevance since an increase in [Cl−]o enhances channel opening when the [Cl−]i is in the physiological range. The ClC‐2 chloride channel is widely expressed in the plasma membrane of mammals. The ClC‐2 protein has two independent pores or conduits to allow the passage of chloride ions. Each pore is controlled by a gate, which is open or closed by changing the voltage across the plasma membrane. For this reason, the function of the ClC‐2 protein is dependent on voltage. Here we demonstrate that this gate responds to voltage because when the voltage is changed a chloride ion move through the conduits to reach and push open the gate. Thus, chloride is the current carrier and a facilitator of gate opening. Determining how chloride regulates ClC‐2 helps to understand the chloride movement into and out of our cells.